Interpretation of gravity anomaly data using the wavelet transform modulus maxima - Chanh, Tin Duong Quoc; Hieu, Dau Duong; Xuan, Vinh Tran (Vietnam Journal of Marine Science and Technology, 2017)
Recently, the continuous wavelet transform has been applied for analysis of potential field data, to determine accurately the position for the anomaly sources and their properties. For gravity anomaly of adjacent sources, they always superimpose upon each other not only in the spatial domain but also in the frequency domain, making the identification of these sources significantly problematic. In this paper, a new mother wavelet function for effective analysis of the locations of the close potential field sources is used. By theoretical modeling, using the wavelet transform modulus maxima (WTMM) method, the relative function between the wavelet scale factor and the depth of gravity source is set up. In addition, the scale parameter normalization in the wavelet coefficients is reconstructed to enhance resolution for the separation of these sources in the scalogram, getting easy detection of their depth. After verifying the reliability of the proposed method on the theoretical models, a process for the location of the adjacent gravity sources using the wavelet transform is presented, and then applied for analyzing the gravity data in the Mekong Delta. The results of this interpretation are consistent with previously published results, but the level of resolution for this technique is quite coincidental with other methods using different geological data.